Unsuccessful therapy of combined mycotic infection in a severely burned patient: a case study - Lipový, B; Rihová, H; Hanslianová, M; Kocmanová, I; Zaloudíková, Z; Kaloudová, Y; Suchánek, I; Mager, R; Krupicová, H; Slezák, M; Datko, M; Brychta, P; et al. (Acta chirurgiae plasticae, 2009)
Patients with burn trauma are always in danger of contracting an infection. Although invasive mycotic infections are not as frequent as bacterial infections, high mortality and in many cases difficult diagnostics pose a serious threat not only for neutropenic patients. In more extensive burns the status is further complicated by specifically compromised immunity. The most frequent species of micromycetes isolated in burn patients are Candida spp. and Aspergillus spp. Zygomycetes represents a relatively uncommon isolation worldwide (up to 2% of all fungi. We present a case study of a young patient with 82% TBSA (total body surface area) burns, where we isolated simultaneously 3 different types of micromycetes (Aspergillus fumigatus, Fusarium sp., Absidia sp.). Mycotic infection is understood primarily as a complication in neutropenic patients and, after prophylactic antibiotic and antimycotic administration, in extensive burn trauma patients. The case ended with the death of the patient due to severe sepsis caused by the multiresistant strain Pseudomonas aeruginosa.
Keywords: dospělí; Pseudomonas Infections; Aspergillus fumigatus; Fusarium; Antifungal Agents; Female; aspergilóza; Adult; ženské pohlaví; lidé; Mycoses; mukormykóza; Treatment Failure; mykózy; infekce v ráně; pseudomonádové infekce; fatální výsledek; Fatal Outcome; Pseudomonas aeruginosa; Burns; neúspěšná terapie; Aspergillosis; Mucormycosis; Absidia; Wound Infection; antifungální látky; popálení; Humans